Exendin-4 inhibits growth and augments apoptosis of ovarian cancer cells - He, Wenjing; Yu, Shuang; Wang, Liantang; He, Mian; Cao, Xiaopei; Li, Yanbing; Xiao, Haipeng (Molecular and cellular endocrinology, 2016)
Glucagon-like peptide (GLP)-1 promotes proliferation and survival in β-cell; however, whether GLP-1 receptor agonists promote growth of human ovarian cancer cells remain unknown. We aimed to explore the effects of GLP-1 agents on ovarian cancer cells. GLP-1 receptor expression in human ovarian cancer tissues was detected by immunohistochemical analysis. The effects of exendin-4, a GLP-1R agonist, were investigated on proliferation, migration and invasion, apoptosis in vitro and tumor formation in nude mice of ovarian cancer cells. Our study demonstrated that GLP-1R expressed in both human ovarian cancer tissues and cell lines. Exendin-4 inhibited growth, migration and invasion and enhanced apoptosis of ovarian cancer cells through inhibition of the PI3K/Akt pathway. And exendin-4 attenuated tumor formation by ovarian cancer cells in vivo. Our study suggests that GLP-1R agonists do not promote the growth of ovarian cancer and may even have anticancer effect on selected diabetic patients with ovarian cancer. •GLP-1R expresses in both human ovarian cancer tissues and cells.•Exendin-4 inhibits growth and enhanced apoptosis of ovarian cancer cells.•Exendin-4 plays an antitumor role via inhibition of Akt activation.